Examining Technology for Teaching and Learning (Journal of Education and Development, 2020)
Much time, money, and attention has been given to the issue of technology in the K-12 classroom. In addition, there is an ever-expanding interest in preparing students for success in a transforming, technology-rich world. In the 21st century technology and education must work together to secure the future for students and society. Society in the 21st century is knowledge-based; learning is critical as knowledge resiliency continually becomes important for survival in the rapidly changing environment. The need for changing traditional approaches to education from the acquisition of short-term skills to proactive programs that infuses technology into the learning are of utmost importance as educators prepare students for the 21st century.